Predominant mycotoxins, mycotoxigenic fungi and climate change related to wine - Paterson, R. R. M. (2018)
Wine is a significant contributor to the economies of many countries. However, the commodity can become contaminated with mycotoxins produced by certain fungi. Most information on mycotoxins in wine is from Spain, Italy and France. Grapes can be infected by mycotoxigenic fungi, of which Aspergillus carbonarius producing ochratoxin A (OTA) is of highest concern. Climate is the most important factor in determining contamination once the fungi are established, with high temperatures being a major factor for OTA contamination: OTA in wine is at higher concentrations in warmer southern Europe than northern. Contamination by fumonisins is a particular concern, related to Aspergillus niger producing these compounds and the fungus being isolated frequently from grapes. Aflatoxins can be present in wine, but patulin is seldom detected. Alternaria mycotoxins (e.g. alternariol) have been frequently observed. There are indications that T-2 toxin may be common. Also, the combined effects of mycotoxins in wine require consideration. No other mycotoxins are currently of concern. Accurate fungal identifications and mycotoxin detection from the fungi are important and a consideration of practical methods are required. There is a diversity of wines that can be contaminated (e.g. red, white, sweet, dry and fortified). The occurrence of OTA is higher in red and sweet than white wines. Steps to control mycotoxins in wine involve good agriculture practices. The effect of climate change on vines and mycotoxins in wine needs urgent consideration by well-constructed modelling studies and expert interpretation of existing data. Reliable models of the effect of climate change on vines is a priority: the health of vines affects mycotoxin contamination. A modelling study of OTA in grapes at higher temperatures over 100 years is required. Progress has been made in reducing OTA in wine. The other mycotoxins require consideration and the effects of climate change will become crucial.